Numerical Analysis of Multi-pass Cold Spinning of Superalloy of Cylindrical Part. (August 2020) - Li, Z X; Shu, X D; Ye, B H
Abstract: In view of the poor plasticity and easy cracking of superalloy at room temperature, the multi-pass cold spinning of cylindrical part was studied. Firstly, the tensile test of superalloy GH3030 is carried out, and the true stress-strain curve is obtained. Then, the numerical models of 250 and 87.5 diameter-thickness ratio blank are established, and the stress and strain field, wall thickness distribution and tool force distribution of the cylindrical part are analyzed and compared. The wrinkle model of 250 diameter-thickness ratio blank was analyzed, and the experiment of 87.5 diameter-thickness ratio blank was carried out. The results show that the wall thickness of the cylindrical part has metal accumulation at the flange, and the thickness of the waist is very small, which is easy to crack under the repeated forming of the roller; the wall thickness distribution of the large diameter-thickness cylindrical part is more uniform, but it has a great challenge to the equipment force and the equipment stiffness. The main reason for the flange wrinkle is staggered distribution of the tangential tensile and compressive stress of the whole flange.